Rancang Bangun Back-End Aplikasi Bank Sampah Trash-Mate Berbasis Android Menggunakan Metode Design Thinking - Ardani, Wayan; Sari, Kadek Diana; Asrowardi, Imam (ROUTERS: Jurnal Sistem dan Teknologi Informasi, 2023)
Trash-Mate is a Waste Bank application that can be a medium of information and facilitate the Waste Bank Customer transaction process more practically and effectively, to help the community in conducting waste management transactions at the Waste Bank remotely through the android application. The features in the Back-End Design for the Android-Based Trash-Mate Waste Bank Application are login, Customer Data, Admin Data, Trash Data, Trash Pickup, Balance Withdrawal, and Log-Out. Basically, a waste bank is a program where waste will be collected and sorted, then the waste will be exchanged for money. The remaining waste will be weighed and valued at a certain amount, then sold to factories that have partnered with waste banks.